EFEKTIFITAS KINERJA LAJUR KHUSUS SEPEDA DI KAWASAN KOTA MEULABOH - Bambang Tripoli; Rahmat Djamaluddin (Universitas Teuku Umar, 2019)
The Meulaboh City Government under the leadership of the Regent H. T. Alaidinsyah (in the period of 2012 - 2017) has a high concern on the use of bicycles as an alternative transportation tool that is cheapand environmentally friendly because it can help reduce congestion, air pollution, and have a positive impact on the health of its riders. The application of special bicycle lanes can be applied but often private vehicles, motorbikes and rickshaws stop blocking the bicycle lane. The use of bicycle lanes for parking vehicles should not be allowed, so cyclists are forced to use dangerous sidewalks or public roads. The problems raised and also become the purpose of research are how much influence the performance of bicycle lanes specifically on the lane of motorized vehicles and the level of effectiveness of their use in the city of Meulaboh. The research boundary was at the data collection location on Tgk Chik Ditiro Street, Pocut Baren, Teuku Umar and Sudirman Street, which is in Johan Pahlawan Subdistrict, West Aceh District (Meulaboh), with a length of 1635 meters of bicycle lanes. The calculation uses the BLOS (Bicycle Level Of Service) method. Based on the results of the research on the Tgk Chik Ditiro road rating of BLOS 3.7 and Teuku Umar road, the rank rating of 4.3 is based on the BLOS < 4.5 value limitation rating, categorized as rank D with the BLOS description of the two road environments that are not feasible for cyclists. Jalan Pocut Baren value generated 3.1 < 3.5 set by BLOS, stated rating C with the description of the environment on the road segment is good enough for cyclists. Whereas for Sudirman road the rating of 1.8 < 2.5 which was set by BLOS, was stated as rank B with the description of the environment on the road section was good for bicycles.